2020
DOI: 10.1002/jbm.a.37097
|View full text |Cite
|
Sign up to set email alerts
|

Advancing continuous subcutaneous insulin infusion in vivo: New insights into tissue challenges

Abstract: Continuous Subcutaneous Insulin Infusion (CSII) is superior to conventional insulin therapy as it improves glycemic control thus reducing the probability of diabetic complications. Notwithstanding CSII's benefits, insulin dependent diabetic patients rarely achieve optimal glucose control. Moreover, CSII is only FDA approved for 3 days and often fails prematurely for reasons that have not been fully elucidated. We hypothesize that phenolic compounds, such as m‐cresol and phenol, which are present in all commerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(69 citation statements)
references
References 32 publications
(70 reference statements)
2
64
0
Order By: Relevance
“… 32 Rodent studies have shown that phenolic compounds found in insulin are associated with increased inflammatory stress and increased leucocyte activation. 33 Insulin antibodies have also been associated with the development of lipohypertrophic tissue. 34 35 It may also be that in people with higher insulin antibodies, localized insulin exposure mediates an inflammatory response causing tissue change.…”
Section: Discussionmentioning
confidence: 99%
“… 32 Rodent studies have shown that phenolic compounds found in insulin are associated with increased inflammatory stress and increased leucocyte activation. 33 Insulin antibodies have also been associated with the development of lipohypertrophic tissue. 34 35 It may also be that in people with higher insulin antibodies, localized insulin exposure mediates an inflammatory response causing tissue change.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] Skin irritation derived from the catheter materials, insulin formulations or mechanical/biophysical properties of the infusion devices and fluids itself, are all possible contributors to the short CSII lifespan (Table 1). 8,9,[11][12][13][14][15] Currently, all commercial CSII compatible insulin formulations contain insulin phenolic preservatives (IPP), (e.g. phenol and/or m-cresol), which stabilize insulin in a hexameric form and thus prevent denaturation and degradation, while maintaining Abbreviations: CSII, Continuous Subcutaneous Insulin Infusion; S, saline; D, diluent; I, insulin; T/S, thioglycolate/saline; T/I, thioglycolate/insulin; PMNs, neutrophils; MQ/ Mo, macrophages/monocytes; IPP, insulin phenolic preservatives.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 However, previous studies in our laboratory have shown that IPP are cytotoxic and induce an inflammatory cascade. 15,18 IPP induces a significant influx of inflammatory cells-specifically neutrophils (PMNs) and macrophages/monocytes (MQ/Mo). 15 Inflammatory cells release proteases that result in protein degradation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations